(3GdGKHGJ GdYdei dLQGFe JRjja hJRhjQ GdeMQQGJ GdJbdjOjI hGdGdcJQhfjI (B: s (3OQGSI YdejI hbGfhfjI hJWHjbjI ebGQfI (B/ s - (3YHOGdfGUQ eMeO eMehO aQZdi s; (3QjGV aJM Gddg HUdI s; (3eMehO cHjTs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JgJe gPg GdQSGdI HYedjI GdGKHGJ GdYdei dLQGFe JRjja hJRhjQ GdeMQQGJ GdJbdjOjI hGdGdcJQhfjI MjK JbOe GdOQGSI YedjI (B- (3afjI hbGfhfjI JWHjbjI JSge ai hVY GdCWQ hGdCSS GdbGfhfjI hGdYdejI GdTQYjI ceG JSge ai JVjjb GdaLhI Hjf GdefXhQ GdbGfhfi (B((3Gdabgi hGdbVGFi (B) (3hHjf GdefXhQ GdYdei Gdafi GdTQYi ai gPG GdeLGd hJfGhd GdHGMK LQGFe JRjja hJRhjQ GdeMQQGJ GdJbdjOjI hGdGdcJQhfjI hGdGWGQ GdbGfhfi ddGKHGJ GdYdei dLQGFe JRjja hJRhjQ GdeMQQGJ GdJbdjOjI hGdGdcJQhfjI Ke GdGWGQ GdJbfi hGdJWHjbi ddGKHGJ GdYdei dLQGFe JRjja hJRhjQ GdeMQQGJ GdJbdjOjI hGdGdcJQhfjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb(B. - (3bSe GdbGfhf GdLfGFi, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B403-426s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdNHQIs; (3GdGKHGJ GdYdei s; (3cTa GdJRhjQ hGdJRjjas; (3JRhjQ GdeMQQGJ GdGdcJQhfjIs; (3GdGKHGJ GdLfGFjs; (3GdNHQI GdbVGFjIs; (3GdOdjd GdLfGFjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs